Teacher Motivation as a Factor in Language Teaching and Learning in Nepal - Sah, Kedar Prasad (Academic Voices: A Multidisciplinary Journal, 2018)
This study was carried out to investigate the level of teacher motivation, the association between teacher motivation and language learning and teaching as well as the policies that provinces have created. The study became necessary in order to assess the impact of policies the provinces have brought regarding the remuneration of school level teachers and other factors. This view is held that there has been no commensurate improvement in student performance in response to government’s gesture. The teachers are found less motivated towards their classroom behavior. Teachers claim that they are not motivated to teach is supported by negative assessment of several variables in teaching/learning environment that are critical in raising and maintaining teacher motivation, teaching efficiency and classroom activities. Academic Voices Vol.6 2016: 1-4